Recent Developments in Molecularly Imprinted Nanoparticles by Surface Imprinting Techniques. Issue 3 (19th August 2013) - Ding, Xiaochu; Heiden, Patricia A.
<x xml:space="preserve">Abstract</x> Molecularly imprinted polymer nanoparticles (MIPNPs) are an increasingly important area of research with potential in applications such as biosensors, solid phase extractions and bioassays. Advantages over the traditional molecularly imprinted polymers typically include a higher binding capacity, greater selectivity and affinity for target species, and aqueous compatibility. Recent research efforts have sought to impart MIPNPs with additional capabilities by introducing nanoparticle size‐control, stimuli‐responsiveness, biocompatibility, and optoelectronic properties. This short review describes the molecular imprinting principle and then discusses recent advances in the field of MIPNPs with particular focus on surface polymerization techniques to imprint both small and macro molecules.<inline-graphic xlink:href="ark:/27927/pgg4svkks5x" content-type="mame201300160-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />